Penyusunan Instrumen Mitigasi Risiko Konsentrasi Pembiayaan Perbankan Syariah Di Indonesia - Astri Afrilia (UIN Sunan Gunung Djati Bandung, 2023)
Currently, Islamic banking has become the choice of the Indonesian people to carry out banking transactions, both depositing funds and applying for financing. Sharia banking assets in recent years have increased by 14.56% or Rp 561 Trillion, mostly contributed by increased financing. In the distribution of financing, there are risks in it, one of which is the risk of financing concentration. This study aims to develop instruments in mitigating the concentration risk of Islamic banking financing in Indonesia. The research method used is quantitative method with data analysis technique used is Process Hierarchy Analysis (AHP). The results of this study are in the form of ranking the distribution of financing per economic sector based on the level of risk required as a guide for Islamic banking to channel risk-based financing.